Os precedentes judiciais e sua relação com a arbitragem - Conceição, Danilo Orenga (2020)
The present study aims to analyze how arbitration can be influenced by judicial precedents. At the beginning, we will analyze the definition of arbitration, its history in Brazil, its main characteristics and most relevant principles. After that, the dissertation analyzes the four possible aspects regarding the nature of arbitration: the autonomous, contractual, jurisdictional and hybrid, highlighting the predominance of the hybrid nature. Then, the research is directed to the analysis of precedents in common law and civil law systems, highlighting the main characteristics of each system, especially with regard to the role of precedents as a primary normative source in the first system and secondary role in the second system. It is also pointed out the main similarities and distinctions in the treatment and use of precedents. Then, the dissertation focus on the precedent system brought by the Civil Procedure Code and its disconnection with the precedents of the common law system, arguing that the acceptance of the precedent system of the Civil Procedure Code as a primary source may imply in the recognition of its unconstitutionality and, therefore, the judicial precedents should be treated as a secondary normative source. Arbitration as a system and its treatment as an independent justice system, albeit in cooperation and coordination with the judicial system are debated. The research still analyzes how judicial precedents of infraconstitutional origin affects arbitration, and why there is no duty to comply with such precedents by the arbitrators. Immediately thereafter, we have addressed the judicial precedents of constitutional origin in abstract constitutional control, by which we justify the arbitrator’s biding due to the normative nature of these decisions, while, in relation to the diffuse control of constitutionality, we have pointed out the lack of binding due to the absence of constitutional support. In this scenario, it is highlighted the restricted scope of the binding precedents, which also do not bind the arbitrators, except for the arbitrations that have the public administration as a party. This investigation concludes by analyzing the judicial remedies that can be used to annul an arbitral award, such as the Constitutional Complaint and the Response to the Request of Enforcement of an Award, where we have pointed out that the Constitutional Complaint is inapplicable as there is no subordination between the arbitration system and the judicial system. As to the Response to the Request of Enforcement of an Award, the study claims it can only be used in exceptional situations. Still, it is affirmed that an arbitration award can only be annulled if it violates a judicial precedent of constitutional origin in abstract control of constitutionality, a situation in which the hypothesis of violation of the arbitration agreement or public order would be verified or, if argued as a relevant argument, the precedent is ignored by the arbitrators, in which case we would have a violation of the duty to properly motivate a decision by the arbitrators. Also noteworthy is the exceptional application of the theory of the manifest disregard of the law as a ground for the annulment of the arbitration award. Finally, it should be noted that, due to the principle of autonomy, the parties can provide in the arbitration clause that the precedents must be observed or not by the arbitrators